Expectations of Shoulder Surgery Are Not Altered by Surgeon Counseling of the Patient - Lawrence, Cassandra; Zmistowski, Benjamin M.; Lazarus, Mark; Abboud, Joseph; Williams, Gerald; Namdari, Surena (Joints, 2017)
Purpose The primary objective of this study was to evaluate if the current mechanisms of preoperative counseling influence patients' expectations of shoulder surgery.Methods Patients were asked to complete the Hospital for Special Surgery's (HSS) Shoulder Surgery Expectations Survey. The first survey was completed before the first appointment with one of four fellowship-trained shoulder surgeons. The second survey was completed after patients consented for surgery. Our analysis also included patient demographics and surgical factors.Results A total of 41 patients completed the HSS Shoulder Surgery Expectations Survey before and after their first appointment with the surgeon during which they consented to shoulder surgery. Before seeing the surgeon, the mean HSS Shoulder Surgery Expectations score was 72.5. After seeing the surgeon and being consented for surgery, the mean HSS Shoulder Surgery Expectations score was 74.8. The mean change in HSS Shoulder Surgery Expectations score (+2.3) was not statistically significant (p value = 0.242). We did not find any significant correlations between patients' expectations and demographics or surgical factors. Total HSS Shoulder Surgery Expectations scores and change in scores were not statistically different between the four surgeons (p = 0.146).Conclusion Patient expectations were not substantially altered after preoperative counseling. Further investigation is necessary to investigate factors correlated with expectations, the implication of unaltered expectations on the postoperative outcome, and methods for improving the preoperative counseling process.Level of Evidence Level II, prospective cohort study.
Keywords: expectations of surgery; preoperative counseling; patient recall; patient comprehension; patient satisfaction; patient education